Composition and measurement of charged atmospheric clusters - Aplin, K (2008)
Atmospheric charged clusters are formed in a series of rapid chemical reactions after ionisation, leaving a central ion X or X clustered with n ligands (Y) . In solar system tropospheres and stratospheres there are two distinct cluster regimes: the terrestrial planets contain largely hydrated clusters (i.e. Y=HO), whereas the gas planets and their moons have organic or nitrogenated cluster species. These classifications are largely based on model predictions, since hardly any measurements are available. The few existing composition measurements are reviewed, including the recent detection of massive charged particles in Titan's upper atmosphere. Technologies for both remote sensing and in situ measurements of atmospheric charged clusters are discussed. Preliminary measurements in the terrestrial atmosphere are presented indicating that ambient charged cluster species interact with downwelling infra-red radiation at 9.15 μm, even in the presence of cloud. This supports the possibility of future infrared detection of charged clusters. © 2008 Springer Science+Business Media B.V.